p53 Regulates a miRNA-Fructose Transporter Axis in Brown Adipose Tissue Under Fasting - Reinisch, Isabel; Klymiuk, Ingeborg; Michenthaler, Helene; Moyschewitz, Elisabeth; Galhuber, Markus; Krstic, Jelena; Domingo, Magnus; Zhang, Fangrong; Karbiener, Michael; Vujić, Nemanja; Kratky, Dagmar; Schreiber, Renate; et al. (Frontiers in Genetics, 2022)
Active thermogenic adipocytes avidly consume energy substrates like fatty acids and glucose to maintain body temperature upon cold exposure. Despite strong evidence for the involvement of brown adipose tissue (BAT) in controlling systemic energy homeostasis upon nutrient excess, it is unclear how the activity of brown adipocytes is regulated in times of nutrient scarcity. Therefore, this study aimed to scrutinize factors that modulate BAT activity to balance thermogenic and energetic needs upon simultaneous fasting and cold stress. For an unbiased view, we performed transcriptomic and miRNA sequencing analyses of BAT from acutely fasted (24 h) mice under mild cold exposure. Combining these data with in-depth bioinformatic analyses and in vitro gain-of-function experiments, we define a previously undescribed axis of p53 inducing miR-92a-1-5p transcription that is highly upregulated by fasting in thermogenic adipocytes. p53, a fasting-responsive transcription factor, was previously shown to control genes involved in the thermogenic program and miR-92a-1-5p was found to negatively correlate with human BAT activity. Here, we identify fructose transporter Slc2a5 as one direct downstream target of this axis and show that fructose can be taken up by and metabolized in brown adipocytes. In sum, this study delineates a fasting-induced pathway involving p53 that transactivates miR-92a-1-5p, which in turn decreases Slc2a5 expression, and suggests fructose as an energy substrate in thermogenic adipocytes.